Dynamic Causal Modeling of Gender Differences in Emotion: Implications for Augmented Cognition. (December 2020) - Huang, Jiali; Lindquist, Kristen; Nam, Chang S.
The goal of this study is to investigate the neural basis of gender difference in emotion processing. Elec- troencephalogram (EEG) signals were recorded when the same set of emotion-eliciting images was shown to male and female participants. Neural connections were estimated using Dynamic Causal Modeling (DCM) and results for both genders were compared. We found that dorsolateral prefrontal cortex exerts modulatory effects differently for males and females. These findings on the gender differences in neural mechanisms of emotion processing may be utilized in applications of the augmented cognition program.